Shallow carbon storage in ancient buried thermokarst in the South Kara Sea - Alexey Portnov (Nature Portfolio, 2018)
Abstract Geophysical data from the South Kara Sea reveal U-shaped erosional structures buried beneath the 50–250 m deep seafloor of the continental shelf across an area of ~32 000 km2. These structures are interpreted as thermokarst, formed in ancient yedoma terrains during Quaternary interglacial periods. Based on comparison to modern yedoma terrains, we suggest that these thermokarst features could have stored approximately 0.5 to 8 Gt carbon during past climate warmings. In the deeper parts of the South Kara Sea (>220 m water depth) the paleo thermokarst structures lie within the present day gas hydrate stability zone, with low bottom water temperatures −1.8 oC) keeping the gas hydrate system in equilibrium. These thermokarst structures and their carbon reservoirs remain stable beneath a Quaternary sediment blanket, yet are potentially sensitive to future Arctic climate changes.